2020
DOI: 10.1097/mcp.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and severe acute respiratory syndrome coronavirus 2019: current evidence and knowledge gaps

Abstract: Purpose of reviewAlthough respiratory viruses are common triggers of asthma exacerbation, it is unknown whether this also applies to infection with SARS-CoV-2. Indeed, patients with asthma and allergy appear underrepresented in large reports of COVID-19 cases worldwide. In this review, we evaluate existing literature on this topic and potential underlying mechanisms for any interrelationship between asthma and COVID-19. Recent findingsData from several preclinical and clinical reports suggest a lower susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
0
15
2
1
Order By: Relevance
“…Interestingly, COVID-19 patients with bronchiectasis showed a significantly higher prevalence of COPD (57.6% versus 19.3%) and asthma (62.1% versus 17.2%) than the overall population with bronchiectasis in South Korea. 10 Although asthmatics were suggested to be protected from COVID-19, 12 this study showed significantly higher asthma rate in COVID-19 patients with bronchiectasis than those without bronchiectasis. Bronchiectasis may serve as a leverage to more severe COVID-19 in asthmatics; however, future research is necessary to clarify the mechanistic link.…”
Section: To the Editorcontrasting
confidence: 52%
“…Interestingly, COVID-19 patients with bronchiectasis showed a significantly higher prevalence of COPD (57.6% versus 19.3%) and asthma (62.1% versus 17.2%) than the overall population with bronchiectasis in South Korea. 10 Although asthmatics were suggested to be protected from COVID-19, 12 this study showed significantly higher asthma rate in COVID-19 patients with bronchiectasis than those without bronchiectasis. Bronchiectasis may serve as a leverage to more severe COVID-19 in asthmatics; however, future research is necessary to clarify the mechanistic link.…”
Section: To the Editorcontrasting
confidence: 52%
“…Recent data suggests differing susceptibility to COVID-19 among asthma patients based on their phenotype, with a lower susceptibility in patients with underlying type 2 airway inflammation [ 3 ]. In our series, wheezing was significantly more frequent in the non-T2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, the organ tropism of SARS-CoV-2 to the respiratory tract could potentially aggravate asthma. In fact, although respiratory viruses are common triggers of asthma exacerbation, it has not yet been established whether this also applies to SARS-CoV-2 infection [ 3 ]. The susceptibility of patients with asthma to develop an exacerbation when they are infected with SARS-CoV-2 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of COVID-19 must include detailed information on asthma comorbidity and prior medication to help answer these questions [125]. Today, there is no evidence of an association of increased risk of COVID-19 infection in asthmatic patients regularly taking ICSs [126]. Asthma exacerbations have been markedly reduced especially in children during the COVID-19 pandemic, which may not only be due to a decrease in exposure to triggers, i.e.…”
Section: Inhaled Antiasthmatic Therapies and Covid-19mentioning
confidence: 99%
“…In hospitals, the use of metered-dose inhalers (MDIs) and dry powder inhalers (DPI) is preferred to nebulizers if patients can perform the breathing maneuvers. If a nebulizer is used, a high-flow nasal cannula is preferable to a face mask and a mouthpiece should be used with a jet or mesh nebulizer, and viral filters or one-way valves should be attached to nebulizers to minimize the release of aerosols [126].…”
Section: Inhaled Antiasthmatic Therapies and Covid-19mentioning
confidence: 99%